Hubungan Self Care pada Pasien Diabetes Melitus Tipe 2 di Poliklinik Penyakit dalam RSU Bhakti Asih Kota Tangerang Tahun 2024 - Shopya Nur Maulidina; Asha Grace Sicilia; Pratiwi Cahya Wardhani; Harun Wahyudi; Usnal Aini (Journal of Educational Innovation and Public Health, 2025)
Diabetes mellitus (DM) is a chronic disease in the form of a metabolic disorder characterized by an increase in blood sugar levels above normal limits. The purpose of this study was to determine the relationship between Self Care and Quality of Life in Type 2 Diabetes Mellitus Patients at the Internal Medicine Polyclinic of Bhakti Asih General Hospital, Tangerang City in 2024. Self care is an independent action that includes diet, exercise, and foot care to control blood sugar. Quality of life is a good or bad condition of diabetes mellitus patients in viewing their disease. The design of this study used a quantitative method with a cross-sectional approach. The population in this study were Diabetes Mellitus patients at the Internal Medicine Polyclinic of Bhakti Asih General Hospital in September 2024, totaling 169 respondents. The sampling technique for this study used purposive sampling. Data analysis used univariate and bivariate analysis using Pearson product moment. The results showed that the majority of self care was good as many as 128 (75.7%) and good quality of life as many as 125 (74.0%). The results of the bivariate analysis showed that there was a relationship between self care and quality of life <0.001. This study concluded that optimal self-care has a positive impact on the quality of life of patients. The results of this study concluded that there is a Relationship between Self-Care and Quality of Life in Type 2 Diabetes Mellitus Patients.